Authentic Happiness at Work: Self- and Peer-Rated Orientations to Happiness, Work Satisfaction, and Stress Coping - Tandler, Nancy; Krauss, Annette; Proyer, René T. (Frontiers in Psychology, 2020)
The authentic happiness theory covers three basic orientations to happiness; namely, the life of pleasure (via hedonism); engagement (via flow-related experiences); and meaning (via eudaimonia). There is broad evidence for a positive relationship between these three orientations and indicators of positive psychological functioning in a variety of life domains. However, their contribution to well-being at work is understudied. The main aim of this study was testing the relationship between self- and peer-rated orientations to happiness, work related well-being (work satisfaction, work stress), and coping strategies. Further possible mediating effects of the coping strategies on the relationship between orientations to happiness and well-being at work were also examined. The sample consisted of 372 German-speaking Swiss adults (60.3% female), aged between 18 and 65 years (M = 38.9, SD = 10.8) with a minimum of 40% full-time employment. For 100 persons, peer-ratings of the orientations to happiness were available. Our results showed that the life of engagement and, to a lesser extent, the life of meaning are related to work satisfaction. The life of pleasure was associated with lower levels of reported work stress. Further, positive associations between self- and peer-rated orientations to happiness (particularly pleasure) and adaptive coping strategies with stress were also found. Mediation analyses showed that the effects of engagement in general and content-related work satisfaction were mediated mainly by control and negative coping, while the association between meaning and resigned work satisfaction was mediated by positive coping. Negative coping fully mediated the association between the pleasurable life and work stress. Overall, our results indicate that employees’ orientations to happiness are of importance for experiencing well-being at work.